Ectopic pregnancies at a tertiary care centre: a five-year retrospective study - Wakode, Shamrao Ramji; Sharma, Sakshi Pramod (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Ectopic Pregnancy results in significant morbidity. Our aim during present study was to understand age wise, parity wise distribution of cases, risk factors, clinical presentation and management of ectopic pregnancy which may be useful in lowering morbidity and mortality. Methods: A five-year retrospective study was done from 2019 to 2023; comprising detailed medical records of detected cases of ectopic pregnancies admitted to the tertiary care centre. Results: Incidence of ectopic pregnancy during present study was 0.40%. 65.48% of ectopic pregnancy cases recorded in the age group of 21-30 years. Majority of parity wise cases were multipara (63.95%). There were no risk factors noted in 34.01% cases. Majority of the cases (65.95%) had one or the other distinguishable risk factor. 21.68% cases had history of Tubectomy, while 19.38% ectopic gestation had history of abortion. Most of the patients presented with clinical presentation of amenorrhoea 59.89%. 55.83% cases had bleeding per vaginum, while 47.71% had pain in abdomen. Most common ectopic pregnancy site was ampulla, with 63.95% cases. Ultrasonic findings showed ruptured ectopic pregnancy in 59.39% cases and unruptured in 30.45%. Regarding mode of management in the cases, surgical management with unilateral total salpingectomy (56.79%) was most commonly performed, followed by salpingoopherectomy (14.81%). Conclusions: Ectopic pregnancy is a common obstetric emergency leading to first trimester morbidity and mortality. Diagnosis of these cases requires a high index of clinical suspicion and early intervention often is lifesaving. Hence, knowledge of the disease related trends and timely management is the key for successful outcomes in such cases.